Kinesiology the skeletal system and muscle function - Muscolino, Joseph E. (Elsevier Inc., 2017)
This title provides a full-colour examination of bones and joints, with over 1200 illustrations which explains how muscles function as movers, antagonists, and stabilizers in the body. Part One covers the fundamentals of structure and motion, including essential terminology that is used in kinesiology. Part Two covers the skeletal system including the makeup of skeletal and fascial tissues. Part Three contains a detailed study of the joints of the body. And lastly, Part Four examines how muscles function. This new edition also boasts an all-new chapter on biomechanics, more than 100 online video clips, and an interactive muscle program. If you want a thorough understanding of muscle function and how to apply that knowledge on the job, then there's no better guide than Muscolino!